Program Pendampingan Pengendalian Kualitas Dodol “D’Tungku” Melalui Pendekatan Sanitasi Pangan - Anik Nur Habyba; Wawan Kurniawan; Triwulandari Satitidjati Dewayana; Lailatus Siami; Ananda Kejora Rotty (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Dodol is classified as a semi-wet snack with a chewy texture and does not last long to be stored because it is susceptible to microbial contamination. Handling dodol from the production process to packaging needs to consider food safety so that its quality can be maintained and food contamination can be avoided. Sanitation Standard Process Procedure (SSOP) is one of the main requirements for food processing, including dodol. Food sanitation is an essential part of the dodol quality control process. This community service (PkM) aims to provide assistance and training to improve the quality of dodol in the